Mundo Do Trabalho Na Agroindustria: Uma Análise Das Condições De Trabalho De Egressos Do Instituto Federal De Educação, Ciência E Tecnologia Do Estado De Mato Grosso - Acosta, Carmen Lucia Coelho [UNIFESP] (2017)
This study is situated in the technological education arena, emphasizing the training of workers for the agroindustry in acapitalist society. The study relies on alumni's reports on theirworking conditions, and establishes relationships back to their professional training in the Agroindustry Technology course from the Federal Institute of Education, Science and Technology (IFMT), in the city of Campo Novo do Parecis -Mato Grosso state. The theoretical-methodological foundation is marxist critical theory, withparticular contribution from work-education focused scholars. Campo Novo do Parecis campus was selected for being the sole town to offer Agroindustry Technology graduation in a state-owned institution. Background data included the course plan and official documents that served as reference for the preparation of the undergraduate professional training proposal. It also included survey results from eight professors and 20 graduates. In the analysis of the course plan along with professors´ survey results, following aspects were considered: reasons which supported the course start; course characterization, objectives and assumptions; expectations for graduate’s profile; curriculum organization; faculty and school infrastructure. The graduates´ survey disclosed individual profiles, work conditions, and training experienced in the course. The analysis refers to the understanding that the course plan follows DCN guidelines for professional technological education, indicating explicit attention to market demands, increasingly science and technology driven. Thus, integration between work, science and technology is viewed to grant access to competences and jobs. Therefore, integration is decomposed to its instrumental dimension to work, and citizenship into a right to acquire such skills. The course curriculum is wide and generalist, enabling the graduate for comprehensive scope, ranging from raw materials selection, through all phases of industrialization, to the quality control of the finished goods. This requires abilities for new product development, decision making, planning, rationalization, maximization, management and control of quality systems. Curriculum reflects the concept of a multipurpose education, valuing specific training disciplines over humanities in a broader sense. Graduates report having a job in the field of training (80%), indicating the course has facilitated labor market access. Research has shown that undergraduate studies alone are not sufficient for better working conditions. Poor working conditions are reflected in long overtime hours, low wages (two minimum wages on average) and weakening of workers' health. In addition, 31.25% are temporary jobs. Course plan analysis and survey results evidences a multipurpose education, i.e. a direct connection between education and work requirements. In the case of a higher education offered by a public institution, it is necessary to broaden the debate on the integrated formation that allows to establish relations between work, science and culture, having as a horizon the humanistic formation that allows the future worker to understand the complexity of the world of the work and act as a driver of the history of his time.